2021
DOI: 10.1001/jamaneurol.2020.4857
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Efficacy, Safety, and Biomarker Outcomes of Atabecestat in Preclinical Alzheimer Disease

Abstract: IMPORTANCE Atabecestat, a nonselective oral β-secretase inhibitor, was evaluated in the EARLY trial for slowing cognitive decline in participants with preclinical Alzheimer disease. Preliminary analyses suggested dose-related cognitive worsening and neuropsychiatric adverse events (AEs). OBJECTIVE To report efficacy, safety, and biomarker findings in the EARLY trial, both on and off atabecestat treatment, with focus on potential recovery of effects on cognition and behavior.DESIGN, SETTING, AND PARTICIPANTS Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 33 publications
(59 reference statements)
2
37
0
Order By: Relevance
“…However, with excessive or prolonged exposure, these protective effects of Aβ could transition to the well-established neurotoxic effects of high Aβ concentrations, overwhelming glial-mediated Aβ clearance pathways, leading to extracellular Aβ deposition. This nuanced interpretation wherein BACE1 and Aβ monomers serve a protective role is consistent with findings from controlled trials in which BACE1 inhibitors paradoxically worsened cognitive decline,[175, 176] despite markedly decreasing CSF Aβ (see description in Table S1 ). [177]…”
Section: Discussionsupporting
confidence: 78%
“…However, with excessive or prolonged exposure, these protective effects of Aβ could transition to the well-established neurotoxic effects of high Aβ concentrations, overwhelming glial-mediated Aβ clearance pathways, leading to extracellular Aβ deposition. This nuanced interpretation wherein BACE1 and Aβ monomers serve a protective role is consistent with findings from controlled trials in which BACE1 inhibitors paradoxically worsened cognitive decline,[175, 176] despite markedly decreasing CSF Aβ (see description in Table S1 ). [177]…”
Section: Discussionsupporting
confidence: 78%
“…Concerning the failure of recent clinical trials, it should be noted that BACE1 inhibitor drugs showed dose‐dependent cognitive worsening (rather than improvement) in prodromal AD populations. 6 , 7 , 8 This was observed for multiple BACE1 inhibitors at the highest dose, most likely indicative of side effects associated with excessive BACE1 inhibition rather than compound‐specific effects. The current clinical dosage achieving up to 90% Aβ reductions seems far higher than needed, given that an APP mutation (A673T) that lowers Aβ in plasma by only 28% can protect against AD and age‐related cognitive decline.…”
Section: Discussionmentioning
confidence: 95%
“… 3 However, BACE1 inhibitor clinical trials have been failing to show beneficial cognitive outcomes first in patients with mild‐to‐moderate AD 4 , 5 and more recently in those with early stages of mild AD or amnesic mild cognitive impairment (MCI) due to AD (prodromal AD). 6 , 7 , 8 Clinical studies are shifting to target further earlier stages such as secondary prevention (presymptomatic populations) and primary prevention (before amyloid build‐up preceding symptoms by ~ 15 years 9 ) of AD. These efforts are, undoubtedly, indispensable for determining the disease stage to start successful BACE1 inhibitor interventions for clinical efficacy, while evaluating the cognitive benefits (if any) in asymptomatic subjects at a risk of developing AD is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mild AD population enrolled may have been too far along in their disease process to respond to a BACE inhibitor treatment. A BACE inhibitor trial was terminated in the preclinical AD population due to findings of dose-related cognitive worsening and neuropsychiatric adverse events [ 31 ], though it has been hypothesized that a viable low dose BACE inhibition regimen could be identified in the future [ 32 ]. A number of other trials, such as the A4 study [ 33 ] or the AHEAD 3–45 Study (NCT04468659) are attempting to target the amyloid pathway with other mechanisms of action in preclinical AD.…”
Section: Discussionmentioning
confidence: 99%